2021
DOI: 10.1029/2021jb022370
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aperiodic Non‐Tidal Atmospheric and Oceanic Loading Deformations on the Stochastic Properties of Global GNSS Vertical Land Motion Time Series

Abstract: Monitoring vertical land motions (VLMs) at the level of 0.1 mm/yr remains one of the most challenging scientific applications of global navigation satellite systems (GNSS). Such small rates of change can result from climatic and tectonic phenomena, and their detection is important to many solid Earth‐related studies, including the prediction of coastal sea‐level change and the understanding of intraplate deformation. Reaching a level of precision allowing to detect such small signals requires a thorough unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 80 publications
4
9
0
Order By: Relevance
“…Then, these oscillations diminish, and the correlation coefficients oscillate around zero. A similar situation was noticed for the position time series by Gobron et al (2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Then, these oscillations diminish, and the correlation coefficients oscillate around zero. A similar situation was noticed for the position time series by Gobron et al (2021).…”
Section: Discussionsupporting
confidence: 80%
“…The correlation coefficients for distances above 1,500 km have no significant features and oscillate around zero. A similar spatial correlation seasonality in GNSS vertical position time estimates was presented in Gobron et al (2021). They showed that spatial correlation is reduced when non-tidal loading corrections are applied, suggesting that the main contributor to the annual signal present in the correlation coefficient is the intrinsic property of atmospheric variability.…”
Section: Spatial Correlation Of Ztd Residualssupporting
confidence: 64%
“…A lower density implies longer and scarcer baselines, inherently less precise because phaseambiguity resolution becomes more difficult as baseline length increases. Recent study also showed that non-tidal atmospheric and oceanic loading deformations affect the stochastic properties of vertical motions in a latitude-depend way, which could explain part of the larger daily scatter observed at the extremes latitude of our network (Gobron et al, 2021). In any case, this analysis of daily scatter suggests that we can actually extract sub-millimetric short-term signals from horizontal time-series, like for instance tiny co-seismic offsets.…”
Section: Quality Of the Solutionmentioning
confidence: 51%
“…Previous related research mainly focused on horizontal crustal deformation restricted by GPS horizontal velocity, however, there are still relatively few results on the vertical tectonic deformation in the Tianshan and Pamir areas, because more complex geophysical effects are involved the vertical land motion (VLM) (Cheng et al., 2020; Gobron et al., 2021; Riddell et al., 2020). In addition, Tianshan and Pamir are covered by a large amount of snow and glaciers (Chen et al., 2019; Farinotti et al., 2015), which are the significant geophysical contribution to the continuous GPS observations.…”
Section: Introductionmentioning
confidence: 99%